Про деякі підходи до персоналізації щодо організації інтерфейсу користувача в автоматизованих системах - Furtat, Yuriy Olegovich; Dyachuk, Olexandr Anatolievich (Kamianets-Podilskyi National Ivan Ohiienko University, 2014)
In modern automated systems, users are often facing the problem of information overload due to the ever increasing amounts of information to be processed in a short time. Working in these conditions affects the quality of users performing their functions in the system and the reliability of the systems themselves.In the article different existing approaches to solving this problem are described and analyzed, which are based on the idea of creating customized tools for users work with information. On the basis of these solutions a complex methodology of information representation and storage forms personalization is suggested, as well as software architecture based on it.